2013
DOI: 10.1159/000349905
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Roots of Acupuncture and Chinese Medicine

Abstract: The earliest historic reference to a dissection of a human cadaver is found in the biography of Emperor Wang Mang 王莾who in 16 C.E. ordered the medical dismembering of the body of a rebel named Wang Sun-Ching (occidental anatomy began only 1,500 years later). Measurements were made of his internal organs, and bamboo rods were inserted into his blood vessels in order to discover where they begin and where they end for the purpose of a better understanding of how to cure diseases. Similar anatomical dissections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In this study, several structures were associated with LI4. Other publications and textbooks have inferred structures at this specific acupoint, (Langevin & Yandow, 2002;Bai et al, 2011;Peuker, Cummings, Klonowska, & Ferreira, 2018;Schnorrenberger, 2013); however, no other studies have looked at a detailed characterization of LI4 with respect to anatomical variation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, several structures were associated with LI4. Other publications and textbooks have inferred structures at this specific acupoint, (Langevin & Yandow, 2002;Bai et al, 2011;Peuker, Cummings, Klonowska, & Ferreira, 2018;Schnorrenberger, 2013); however, no other studies have looked at a detailed characterization of LI4 with respect to anatomical variation.…”
Section: Discussionmentioning
confidence: 98%
“…Some researchers associate specific conduits of connective tissue as an anatomical basis for acupoints; however, these are purely theoretical and provide loose anatomical associations with specific acupoints (Bai et al, 2011;Langevin & Yandow, 2002). The physiological processes that take place such as central or peripheral reflexes, or changes in systemic or local circulation are dependent upon the aforementioned structures at LI4 (Schnorrenberger, 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…They measured the sizes and weights of the internal organs (Yu, Chen, & Zhao, 2015). Also, they inserted bamboo rods into the veins, aimed to discover the start and end of the vein, for better understanding the therapeutic method related to veins (Schnorrenberger, 2013).…”
Section: Wang Mang and Cadaver Dissectionmentioning
confidence: 99%
“…Although the meridian's essence has not yet been clarified, most scholars have confirmed that the meridian system is a conduction system, different from blood vessels and nerves in humans (Li, Li, Chen, Guo, & Silberstein, 2019). The start and end of the meridians and the flow route of Qi are all based on anatomy (Yang, Li, Nilius, & Li, 2011); there is a close relationship between the meridian's actions and its corresponding spinal nerve and autonomic nervous functions (Marcelli, 2013;Schnorrenberger, 2013). Furthermore, the meridian's physiological functions and pathological changes are also derived and deduced based on anatomy.…”
Section: Influence On the Formation Of Meridian Theorymentioning
confidence: 99%
“…From acupoint localisation and needling techniques to the teaching of acupuncture, the ancient methods are passing down through TCM heritage. Historically, the first standardised acupuncture model was constructed a thousand years ago in 1027 AD (Schnorrenberger, 2013). Produced by metal copper craftsmen, this first model which was about 1,750 mm tall was constructed by Wang Weiyi under the order of Emperor Renzong of the Song Dynasty of China.…”
Section: Introductionmentioning
confidence: 99%